On some Ramanujan identities for the ratios of Eta-functions - Bhargava, S.; Vasuk, K.R.; Rajanna, K.R. (Український математичний журнал, 2014)
We give direct proofs of some of Ramanujan’s P-Q modular equations based on simply proved elementary identities from Chapter 16 of his Second Notebook.